Suicide and Repeated Suicide Attempt in Intoxicated Patients: An Epidemiological Survey in a Tertiary Center - Yekesadat, Seyedmeysam; Ramezani, Maral; Shadnia, Shahin; Hassanian Moghaddam, Hossein; Zamani, Nasim; Erfan Talab Evini, Peyman; Nazemi, Farzad; Rahimi, Mitra (International Journal of Medical Toxicology and Forensic Medicine, 2022)
Background: Suicide is one of the most important psychological emergencies and it is necessary to deal with it. The goal of this study was to evaluate the frequency of suicide attempts, suicide re-attempt, and guesstimated risk factors in suicidal patients in the poisoning ward of Loghman Hakim Hospital. Methods: This study was performed on suicidal patients in Loghman Hakim hospital in 2021 (January to August). The suicide attempt and the type of mental disorder were confirmed by a psychiatrist and the data sheets were completed. The sample size was 500 cases based on previous similar studies. Results: Three hundred fifteen cases attempted suicide for the first time and 185 had a history of suicide. In both groups, the numbers of women were significantly more than men. In addition, 196 cases of the first group and 121 cases of the second group were under 30 years old and 65.1% of cases with first-time suicides and 62.2% of cases with suicide re-attempts were unemployed. In both groups, the most common drug for suicide was benzodiazepines (30.5% and 21.6%). Unfortunately, two patients died. Also, 67.6% in the first-time suicide attempt group and 57.3% in the suicide re-attempt group had adjustment disorder. No significant differences were observed between both groups in terms of gender, age, marital status, education, chronic disease, drug and habit history, employment status, diagnosed mental disorder, and type of drug used for the current suicide. Conclusion: Young age, unemployment, mental disorders (especially adjustment disorder), and female gender are the most important risk factors for a suicide attempt and re-attempt.